From bureaucratic forms towards team-based knowledge work systems: implications for human resource management. (19th November 2009) - Erhardt, Niclas L.; Martin-Rios, Carlos; Way, Sean A.
Teamwork as knowledge integrating mechanisms is critical for firms pursuing a knowledge driven strategy (Grant, 1996b); yet, theoretical and empirical research regarding how to manage knowledge processes in team settings remains limited in the strategic human resource management (SHRM) field. This paper builds on the knowledge work and SHRM literatures. We outline key knowledge processes including knowledge sharing, knowledge creation and team learning. A team-based HRM system is demarcated that aims to foster knowledge work. Four key HR practices are discussed including knowledge staffing, knowledge-based performance management, fostering of shared leadership and trust building. The paper identifies key challenges for HRM and addresses areas for future research.